Molecular Typing of Cronobacter Strains from Food in China by Enterobacterial Repetitive Intergenic Consensus Sequence PCR (ERIC‐PCR) and Sequence Analysis of the gyrB Gene. Issue 4 (22nd October 2013) - Chen, Wanyi; Ai, Lianzhong; Yang, Jielin; Ren, Jing; Li, Yunfei; Guo, Benheng
Abstract The occurrence of outbreaks of Cronobacter strains causing necrotizing meningitis in China highlights the need for strain characterization and subtyping of this pathogenic species. A total of 43 Cronobacter isolates and five Enterobacteriaceae strains were used in this study. The strains were characterized using two molecular typing methods, including enterobacterial repetitive intergenic consensus sequence polymerase chain reaction (ERIC‐PCR) and sequence analysis of the gyrB gene. Genetic profiles of cluster analysis from these two molecular typing tests clearly showed that there was no close relationship between Cronobacter spp. and Enterobacteriaceae strains. Discriminatory index of ERIC‐PCR typing for the 43 Cronobacter isolates and five Enterobacteriaceae strains was high (D = 0.984) by Simpson's index of diversity based on the similarity value of more than 80% using BioNumerics version 5.0. Sequence analysis of the gyrB gene was proven to be suitable for the phylogenetic analysis of the Cronobacter strains. These results demonstrate that ERIC‐PCR combined with sequence analysis of the gyrB gene may be a reliable, rapid typing strategy for Cronobacter strains. Practical Applications Molecular typing of foodborne pathogenic bacteria has been shown as a useful tool for tracking the source of infection and detection of virulent strains, as well as for determining the geographical and host distribution of possible variants. ERIC‐PCR provides rapid clustered results when a large number of Cronobacter spp. isolates need to be subtyped rapidly. Furthermore, partial sequence analysis of the gyrB gene was utilized to differentiate among the closely related isolates. The results of the current study suggest that ERIC‐PCR in conjunction with the gyrB sequence analysis would provide a reliable and accurate typing strategy for Cronobacter spp. strains. This combination of techniques can be used as a rapid means of comparing Cronobacter spp. isolates for epidemiological investigations.